Structure optimization of plough blades in a ploughshare mixer using the DEM simulations. Issue 9 (3rd June 2020) - Fang, Ziqiang; Peng, Songlin; Yi, Jiangang; Du, Jun
Abstract : Purpose: The purpose of this paper is to optimize the structure of plough blades in a ploughshare mixer using the discrete element method (DEM) simulations. Design/methodology/approach: Using the validated DEM model, three numerical tests are conducted to determine how the mixing performance evolves as structural parameters of blades change. Results from the analysis provide basis for structure optimization of blades. The structural parameters include sweep angle of blade γ, regular axial pitch p and regular circumferential angular offset α . The parameters to evaluate mixing performance include mass flow rate and Lacey index. Findings: The DEM results show that the mixing performance at γ of 35° is better than 15°, 25° and 45°. The mixer which has a p of less than or equal to 1.11 ·  b is more efficient than the mixer which has a p greater than 1.11 ·  b, where b is tail width of blade. The circumferential symmetric distribution of blades ( α = 180°) is more beneficial to improve the mixing performance in comparison with the circumferential asymmetric distribution ( α < 180°). Based on the results, an optimized mixer with a γ of 35°, a p of 0.61 ·  b and an α of 180° is proposed, which has a better mixing performance compared to all mixers listed. Originality/value: The structural parameters of blades, including γ, p and α, are found to be critical for good mixing. From the view angle of structure optimization of plough blades, a new ploughshare mixer with a γ of 35°, a p of 0.61 ·  b and an α of 180° is investigated and recommended for improving mixing efficiency.